PENGUJIAN WEBSITE INVITEES MENGGUNAKAN METODE LOAD TESTING DENGAN APACHE JMETER - Wanta Tejaya; Syaiful Rahman; Abdul Munir (KHARISMA Tech, 2023)
The purpose of this research is to do a performance test on the Invitees website and how optimal the load time is on the main function of the invitees website. This test was conducted using the Load Testing method with the Apache Jmeter tool. The load time obtained from the test is then compared with the test target to find out how optimal the load time of the Invitees website is. From the test, it was obtained that the average load time of the invitees website when the service was used, represented by the first and second scenarios, had met the test target, which was under 3 seconds. As for the results based on the third scenario which represents the condition of the service used with twice as many user loads, the average load time does not meet the test target. So it can be concluded that the Invitees website has worked optimally when the service is used but still needs to be improved if the service is used by more users.